The long-term impact of coaching in an executive MBA program - Julia A. Fulmore; Jude Olson; Linda LaCoste (Organization Management Journal (OMJ), 2022)
Purpose - The purpose of this qualitative study is to conduct an exploratory investigation of the impact and sustainability of coaching on career and leadership development of students and later, alumni, in an Executive Master of Business Administration (EMBA) program. Design/methodology/approach - The sample for this qualitative study consisted of 14 alumni of an EMBA program at a private university in the Southwestern US who graduated between January 2012 and May 2019. Eleven alumni participated in the focus groups, and three alumni participated in personal interviews. Findings - The open coding of the data resulted in three emergent themes (personal development by overcoming personal deficiencies, coaching translates to learning about leadership and coaching motivates sustained change) that confirmed the positive long-term effect of coaching as part of an EMBA program. Practical implications - By participating in an executive coaching engagement, the EMBA students learned a development process that they could repeat for themselves after graduation and transfer to others. In addition, the EMBA students were able to leverage knowledge gained from the coaching experience for the development of others. Originality/value - While the positive impacts of coaching are well-documented, its long-term impact on EMBA students/alumni has not yet been studied. This study builds on other evaluative studies to identify the benefits of executive coaching.
Keywords: 650; Coaching; Coaching outcomes; Executive coaching; Executive education; Executive MBA; Leadership development; Long-term effects of coaching; Sustained change; Transformative adult learning